2017
DOI: 10.1111/jvim.14831
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis in 715 Dogs (2011–2015)

Abstract: BackgroundThrombocytosis is a hematologic abnormality in dogs that has been associated with various neoplastic, metabolic, and inflammatory conditions.ObjectiveTo classify thrombocytosis in dogs based on severity and evaluate whether there are associations between severity and underlying disease processes.AnimalsSeven hundred and fifteen dogs with thrombocytosis and 1,430 dogs with normal numbers of platelets.MethodsRetrospective study. Medical records of dogs with increased (>500 × 103/μL; thrombocytosis grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 43 publications
6
42
2
3
Order By: Relevance
“…; Matowicka‐Karna ; Woolcock et al . ). Previous studies in people have reported increases in platelet count and fibrinogen levels as a marker of inflammation and associated with more severe disease in various conditions including neoplasia, acute coronary syndrome, and inflammatory bowel disease (Odeberg et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Matowicka‐Karna ; Woolcock et al . ). Previous studies in people have reported increases in platelet count and fibrinogen levels as a marker of inflammation and associated with more severe disease in various conditions including neoplasia, acute coronary syndrome, and inflammatory bowel disease (Odeberg et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, future studies, including blood smears and flow cytometry, should be performed to assess this platelet increase and if there is any change to platelet function following RIV administration before drawing any specific conclusions regarding RIV's effect on platelets. Increases in platelet count are frequently associated with inflammation as well (Schafer 2001;Jagadesham et al 2014;Matowicka-Karna 2016;Woolcock et al 2017). Previous studies in people have reported increases in platelet count and fibrinogen levels as a marker of inflammation and associated with more severe disease in various conditions including neoplasia, acute coronary syndrome, and inflammatory bowel disease (Odeberg et al 2016;Suzuki (Morassi et al 2016) and therefore theoretically could worsen the underlying disease process.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of these other myelosuppressive drugs at weekly intervals from vincristine treatments may have altered platelet counts. Prednisone was also administered at tapering doses during the first 4 weeks of treatment, which may be a potential confounder because thrombocytosis is commonly reported in dogs receiving corticosteroids (Woolcock et al 2017). The tumour burden was differed between the beginning of treatment and when remission was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytosis is a rare condition in dogs with malignant neoplasia [5], but typically occurs in humans with cancer [6]. However, there ports presented in the literature are conflicting, as some authors suggest that thrombocytopenia is the most common abnormality in dogs with malignant disease [5], while others indicate that thrombocytosis is a frequent abnormality in dogs with cancer [18,21,27]; thus, the true prevalence of thrombocytosis in animals with neoplasia might be underreported [5].…”
Section: Discussionmentioning
confidence: 99%